Canteen Banter or Racism: is there a Relationship between Oslo Police's Use of Derogatory Terms and their Attitudes and Conduct towards Ethnic Minorities? - Sollund, Ragnhild (Journal of Scandinavian studies in criminology and crime prevention, 2007)
This paper explores the possible connection between the Oslo police's use of derogatory terms about the ethnic minority population, and actual police attitudes and conduct. The article's background is a research project focusing on the relationship between the police and Oslo's ethnic minorities. Qualitative methods were applied, including observations amongst rank-and-file officers in three police stations, interviews with 20 police officers of different rank and gender, as well as interviews with three samples of basically ethnic minority men. The background for the police's use of derogatory terms about the ethnic minority population is discussed, and possible institutional support is explored. The canteen language and attitudes towards ethnic minorities are seen in relationship to police experiences with them. Incidents observed during the field-work are applied in the discussion of whether the police conduct may be influenced by their language and thus lead to unjustifiable targeting of ethnic minorities for stop and search. The observations of police conduct are perceived in the light of ethnic minority informants' police experiences. Although a direct connection between derogatory terms and actual conduct was not confirmed through the observations, the ethnic minority informant interviews suggest that such a connection may not be discarded and such language must therefore be avoided as it may increase the social distance between the police and ethnic minorities